Intake of phthalate-tainted foods alters thyroid functions in Taiwanese children. - Ming-Tsang Wu; Chia-Fang Wu; Bai-Hsiun Chen; Eric K Chen; Yi-Ling Chen; Jentaie Shiea; Wei-Te Lee; Mei-Chyn Chao; Jiunn-Ren Wu (PLoS ONE, 2013)
BACKGROUND: On April-May, 2011, two Taiwan chemical companies were found to have intentionally added phthalates, Di-(2-ethylhexyl) phthalate (DEHP) and/or Di-isononyl phthalate, as a substitute of emulsifier to many foodstuffs. This study aimed to investigate whether exposure to these foods altered endocrine functions in children aged ≤10 years and, if so, whether those changes could be reversed by stopping exposure. METHODS: One Phthalates Clinic for Children was established in southern Taiwan between May 31 and June 17, 2011. All eligible children had their exposure information, blood and/or urine specimens collected. Endocrine functions were assessed in serum. The exposure groups were categorized into three (High, >500 ppm, Low, 1-500 ppm, and No, <1 ppm of DEHP). After six months, some children were followed up for the selected endocrine hormones. RESULTS: Sixty children were eligible in this study; all were Tanner stage 1 with no pubic hair. Compared to non-exposed group, both high and low exposure groups had significantly lower serum thyroid-stimulating hormone (TSH) levels (P = 0.001 and 0.024). At six months follow-up, serum triiodothyronine (T3) levels was significantly changed (P = 0.034) in high exposure group (n = 13). For serum estradiol (E2), the detectable rate (≥8 pg/mL) decreased from 76.9% (10/13) to 30.8% (4/13) (P = 0.070). CONCLUSIONS: This study shows that serum TSH levels can be altered when children were exposed to high concentrations of phthalate-tainted foodstuffs. Serum E2 and T3 may be partially recovered after stopping exposure.